Product Profiles, Traits, and Adoption: Towards a Multi-stakeholder Approach - Najjar, Dina; Agarwal, Shiv (International Center for Agricultural Research in the Dry Areas, 2022)
A presentation on trait Preferences and lentil varietal adoption in Central Ethiopia